A Fine-Grained Model to Assess Learner-Content and Methodology Satisfaction in Distance Education. - Cantabella, Magdalena; Martínez España, Raquel; López, Belén; Muñoz, Andrés (International Journal of Interactive Multimedia and Artificial Intelligence, 2020)
Learning Management System (LMS) platforms have led to a transformation in Universities in the last decade, helping them to adapt and expand their services to new technological challenges. These platforms have made possible the expansion of distance education. A current trend in this area is focused on the evaluation and improvement of the students’ satisfaction. In this work a new tool to assess student satisfaction using emoticons (smileys) is proposed to evaluate the quality of the learning content and the methodology at unit level for any course and at any time. The results indicate that the assessment of student satisfaction is sensitive to the period when the survey is performed and to the student’s study level. Moreover, the results of this new proposal are compared to the satisfaction results using traditional surveys, showing different results due to a more accuracy and flexibility when using the tool proposed in this work.